Bande de filles girlhood identities in contemporary France - Smith, Frances (Routledge, Taylor & Francis Group, 2020)
"Few films in the twenty-first century have represented coming-of-age with the beauty and brutality of Bande de Filles (or Girlhood). This book provides an in-depth examination of Céline Sciamma's film, focusing on its portrayal of female adolescence in contemporary Paris. Motivated by the absence of black female characters in French cinema, Sciamma represents the lives of figures that have passed largely unnoticed on the big screen. While observing the girls' tough circumstances, Sciamma's film emphasises the joy and camaraderie found in female friendships. This book places Girlhood in its cinematic, as well as its sociocultural context. Pop music, urban violence, and female friendships are all considered here in a book draws out the complexity of Sciamma's deceptively simple portrayal of coming-of-age. Thoughtful, concise, and deeply contemporary, this book is perfect for students, scholars, and general readers interested in youth cultures, European cinema, gender and sexuality"--
Keywords: Bande de filles -- Film; Weibliche Jugend -- Motiv; Schwarze Frau -- Motiv; Jugendfilm; Frankreich; Sciamma, Céline / 1980- / Criticism and interpretation; Bande de filles (Motion picture); Coming-of-age films / France / History and criticism; Teenage girls in motion pictures; Teenage girls, Black / France / Paris / Social conditions / 21st century; Motion pictures / France / History / 21st century; Coming-of-age films; Motion pictures; France; France / Paris; 2000-2099; Criticism, interpretation, etc; History